2016
DOI: 10.4103/2277-9175.178806
|View full text |Cite
|
Sign up to set email alerts
|

Compare the educational achievement of medical students with different circadian rhythms in difficult courses of basic sciences

Abstract: Background:Advantageous times for different people are different to some extent, considering the effective physiological changes during the circadian rhythm, in terms of the peak time of physiological activities. The goal of this study is to compare the educational achievement of students, with different morning–evening habits, in completing difficult and easy courses.Materials and Methods:This research is a retrospective descriptive–analytical study, which has been conducted on students of the fifth semester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The distribution between chronotypes is similar to that found in literature [ 5 , 6 ], with 52.7–63% of our students belonging to neither type. However, we found differences between the majors, with RN students having a similar distribution of morning and evening types, and a larger proportion of students adhering to neither type.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The distribution between chronotypes is similar to that found in literature [ 5 , 6 ], with 52.7–63% of our students belonging to neither type. However, we found differences between the majors, with RN students having a similar distribution of morning and evening types, and a larger proportion of students adhering to neither type.…”
Section: Discussionsupporting
confidence: 90%
“…About 60% of the adult population is classified as neither type, while 40% are in one of the two extreme groups [ 1 ]. Studies show that most medical students (52.6% to 67.2%) are neither type [ 5 , 6 , 7 ], which is similar to the adult population.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is based on cortisol levels which increased earlier and have higher amplitude in morning chronotypes than in evening chronotypes; therefore, morningness-oriented students reach their peak performances in the morning hours and eveningness-oriented students have a peak performances in the afternoon (Hasher et al, 2005). Liaghatdar et al (2016) conducted research among medical students and concluded that evening students experienced academic failure in difficult courses, which required a more cognitive performance so there was a proposal to change the class hours of difficult specialized courses to the middle of the day. Enhancing the understanding and remembering abilities of morning and evening people were studied, and results of this study showed that immediate memory of morning people had a better performance in the early hours of the day and that of the evening people had a better performance in the evening hours (Song et al (2000).…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted at the University of Zurich led by Steven Brown (Roenneberg, 2012) showed that the natural biological rhythms of 50% of participants in the study were more or less out of step, and these participants often reported suffering from problems of insomnia or insufficient ability to concentrate on a task. Liaghatdar et al (2016) also described the sleep-wake rhythm and internal rhythm of the body as having an effect on the cognitive activities of people and different people show different performances at different hours of the day. So everyone's body clock is not the same, therefore some difficulties synchronizing natural rhythms with daily plans can exist.…”
Section: Introductionmentioning
confidence: 99%
“…The n-back task has been used to examine working memory processing by looking at the P3 to detect differences in the working memory processingload [4]. Both the comparison and calculation arithmetic task can measure cognitive effort through the oscillatory power in theta and alpha frequencies [5]. The use of these tests can help determine the effects that the circadian rhythm has on cognitive function at various times of the day [6].…”
Section: Introductionmentioning
confidence: 99%